Optimization of Early Children's Fine Motor Development Through Coloring Activities - Daulay, Lily Sardiani; Khadijah, Khadijah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This research was conducted to optimize fine motor development through coloring activities at TKIT Zia Salsabila, Percut Sei Tuan District, Deli Serdang Regency. This research is qualitative with a case study approach. The research was conducted at TKIT Zia Salsabila, Percut Sei Tuan District, Deli Serdang Regency. The research data is in the form of coloring activities by TKIT Zia Salsabila students—sources of data obtained from students and teachers. Observation, interviews, and documentation carry out data collection techniques. At the same time, data analysis is done through data reduction, data presentation, drawing conclusions, and verification. The research results mention the coloring activities carried out at TKIT Zia Salsabila show that coloring activities are considered capable of optimizing children's fine motor development, so that coloring activities must be carried out regularly by parents and class teachers so that children's fine motor skills develop optimally.